Does time to surgery for traumatic hip fracture impact the efficacy of fascia iliaca blocks? A brief report - Kristin Salottolo; Robert M Madayag; Allen Tanner; David Bar-Or; Richard Meinig; Landon Fine; Francie Ekengren; Kerrick Akinola (Trauma Surgery & Acute Care Open)
Objectives Outcomes after traumatic hip fracture have shown to be significantly improved with timely surgical management. This study determined whether there were differences in efficacy of fascia iliaca compartment block (FICB) on pain outcomes in patients with hip fracture, once stratified by time to surgery.Methods Trauma patients (55–90 years) admitted to five Level I/II trauma centers within 12 hours of hip fracture were included. Patients with coagulopathy, significant multi-trauma (injury severity score >16), bilateral hip fractures, and postoperative FICBs were excluded. The primary exposure was analgesia modality: adjunctive FICB or systemic analgesics (no FICB). Study endpoints were incidence of delirium through 48 hours postoperatively (%), preoperative and postoperative oral morphine equivalents (OMEs), and preoperative and postoperative pain (0–10 scale). Adjusted regression models were used to examine the effect of FICB on outcomes; all models were stratified by time from arrival to surgery, ≤24 hours (earlier surgery; n=413) and >24 hours (later surgery; n=143).Results FICB use was similar with earlier and later surgery (70.2% vs 76.2%), and there were no demographic differences by utilization of FICB, by time to surgery. In the earlier surgery group, preoperative pain was lower for patients with FICB versus no FICB (3.6 vs 4.5, p<0.001), with no difference by FICB for delirium (OR 1.00, p>0.99) or OMEs (p=0.75 preoperative, p=0.91 postoperative). In the later surgery group, there was a nearly twofold reduction in preoperative OMEs with FICB than no FICB (25.5 mg vs 45.2 mg, p=0.04), with no differences for delirium (OR 4.21, p=0.18), pain scores (p=0.25 preoperative, p=0.27 postoperative), and postoperative OMEs (p=0.34).Conclusions Compared with systemic analgesia, FICB resulted in improved pain scores at the preoperative assessment among patients with earlier surgery, whereas FICB reduced opioid consumption over the preoperative period only when surgery was later than 24 hours from arrival.Level of evidence II, prospective, therapeutic.